1995
DOI: 10.1002/smi.2460110142
|View full text |Cite
|
Sign up to set email alerts
|

Identifying A psychological profile of Type A behaviour pattern

Abstract: A conceptual model of Type A behaviour pattern (TABP) is presented which frames the pattern in terms of current cognitive‐behavioural psychology and in the wider context of the psychosocial risk factors of CHD. Type A behaviours are considered as stemming from Type A appraisals, elicited in specific situations in individuals with enhanced emotional reactivity who hold a system of beliefs identifiable as Type A. A study was performed in order to assess the possible associations of personality dimensions such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Similarly, Martin, Kuiper, and Westra (1989) found associations between subscales of the DAS and measures of Type A behavior. In an Italian study, a sample of male professional workers classified as fitting the Type A behavior pattern scored higher on factors of the DAS than participants in the same cohort who did not fit the pattern (Sibilia, Picozzi, & Nardi, 1995). Finally, consistent with the cognitive formulation of specific personality disorders (Beck, Freeman, et al, 1990), O' Leary et al (1991) found higher DAS scores in participants diagnosed with borderline personality disorder with and without major depression than in control participants without a personality disorder, although the groups with and without major depression did not differ from each other.…”
Section: Dysfunctional Attitudes In Depression and Other Forms Of Psy...mentioning
confidence: 95%
“…Similarly, Martin, Kuiper, and Westra (1989) found associations between subscales of the DAS and measures of Type A behavior. In an Italian study, a sample of male professional workers classified as fitting the Type A behavior pattern scored higher on factors of the DAS than participants in the same cohort who did not fit the pattern (Sibilia, Picozzi, & Nardi, 1995). Finally, consistent with the cognitive formulation of specific personality disorders (Beck, Freeman, et al, 1990), O' Leary et al (1991) found higher DAS scores in participants diagnosed with borderline personality disorder with and without major depression than in control participants without a personality disorder, although the groups with and without major depression did not differ from each other.…”
Section: Dysfunctional Attitudes In Depression and Other Forms Of Psy...mentioning
confidence: 95%
“…Using a five-factor inventory, Morrison (1997) found that a Type A measure was negatively correlated with Agreeableness but found no correlation with Neuroticism. However, Byrne (1996) as well as Sibilia, Picozzi, and Nardi (1995) reported that Type A personality was positively correlated with Neuroticism.…”
Section: Personality Variables In the Current Meta-analysismentioning
confidence: 97%
“…Although global Type A behavior has been fairly consistent in showing a modest relationship with a number of physiological, health, and work-related variables (Jamal, in press), it has recently been suggested that because of the multidimensional nature of Type A behavior pattern (TABP), the usage of the component measures of Type A behavior might improve the predictive validity of the Type A behavior construct (Edwards & Baglioni, 1991). There are only a few studies in existence in which both the global Type A measure and the component measures of Type A were used (Anderson & Meininger, 1993; Barling & Charbonneau, 1992; Birks & Roger, 2000; Edwards & Baglioni, 1991; Jamal & Baba, 2001; Lee et al, 1996; Sibilia, Picozzi, & Nardi, 1995; Spence, Helmreich, & Pred, 1987). Most of these studies used physiological and health variables as dependent variables.…”
mentioning
confidence: 99%